The Effects of Exclusive Breastfeeding and Contextual Factor of Village on Stunting in Bontang, East Kalimantan, Indonesia - Joko Sugiyanto; Setyo Sri Raharjo; Yulia Lanti Retno Dewi (Journal of Epidemiology and Public Health, 2019)
Background: Basic Health Research Results of 2018 stated that 30.8% of Indonesian children experienced Stunting. Stunting problems describe the existence of chronic nutritional problems, which can be influenced by a variety of interrelated factors. This study aimed to examine the determinants of stunting Bontang, East Kalimantan, Indonesia.Subjects and Method: This was an analytic observational study with a case control design. It was conducted at 15 sub-districts in Bontang, East Kalimantan, from February to April 2019. A sample of 225 children was selected by purposive sampling. The dependent variable was stunting. The independent variables were exclusive breastfeeding, history of infection, low birth weight (LBW), economic status, maternal education, maternal height, basic sanitation, and Community Based Total Sanitation (CBTS) urban village status. The data were collected by questionnaire and analyzed by a multilevel multiple logistic regression.Results: The risk of stunting decreased with maternal height ?150 cm (b = -1.37; 95% CI= -2.41 to -0.32; p = 0.010), maternal education ?senior high school (b = -1.83; 95 % CI= -2.79 to -0.87; p<0.001), exclusive breastfeeding (b= -1.67; 95% CI= -3.28 to -0.06; p= 0.042), and high economic status (b= -1.33; 95% CI= -2.23 to -0.41; p= 0.004). It was increased with number of family members >4 (b= 1.32; 95% CI= 0.41 to 2.22; p= 0.004), history of infectious disease (b= 2.23; 95% CI= 1.32 to 3.14; p<0.001), poor environmental sanitation (b= 1.83; 95% CI= 0.64 to 3.02; p= 0.003), and LBW (b= 1.30; 95% CI= 0.04 to 2.56; p= 0.043). Subdistricts had neglected contextual effect on the incidence of stunting with ICC <1%.Conclusion: The risk of stunting decreases with maternal height ?150 cm, maternal education ?senior high school, exclusive breastfeeding, and high economic status. It is increased with number of family members >4, history of infectious disease, poor environmental sanitation, and LBW. Subdistricts has neglected contextual effect on the incidence of stunting.Keywords: stunting,exclusive breastfeeding, multilevel analysisCorrespondence: